The Role of Buddhist Sunday School Education Policy During The Covid-19 Pandemic for Buddhists in Windu Paramita Bogor - I Ketut Damana (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2022)
The purpose of education is a conscious, planned effort to embody its role in educational policy actively even during the Covid-19 pandemic. Problems in researching the role of Sunday school policies during the Covid-19 pandemic at the Windu Paramita monastery. Educational policies purpose to contribute to Buddhists. This research method uses a descriptive qualitative approach by using a case study model that emphasizes the speed of in-depth policy making involving sources of information. Data collection techniques are carried out through observation, interviews, and documentation. The findings of education have an impact on the weakness of Buddhist policies in Sunday schools such as; the form of education policy, the factors that influence of educational policy, the constraints that affect of educational policy, the response of Buddhists that affect of Buddhist Sunday school education policies during the Covid-19. Tujuan kebijakan pendidikan adalah usaha sadar, terencana untuk mewujudkan peran secara aktif walaupun pada masa pandemic covid-19. Permasalahan dalam peneltian ini berkaitan dengan peranan kebijakan sekolah minggu di masa pandemi covid-19 vihara Windu Paramita ini dikarenakan fakor umat Buddha yang hanya menjalankan tradisi protokol kesehatan tapi tidak tahu maknanya. Hal ini menyebabkan kebijakan kependidikan kurang memberikan kontribusi pada umat Buddha. Sumber data penelitian dalam wujud data primer dan sekunder. Metode penelitian ini menggunakan pendekatan kualitatif deskriptif dengan menggunakan model studi kasus yang menekankan terhadap tergesa-gesa pengambilan kebijakan secara mendalam yang melibatkan sumber informasi. Teknik pengumpulan data dilakukan melalui observasi, wawancara, dan dukumentasi. Hasil temuan kebijakan kependidikan umat Buddha pada sekolah minggu seperti: bentuk peranan kebijakan pendidikan, faktor-faktor yang mempengaruhi peranan kebijakan kependidikan, kendala yang mempengaruhi peranan kebijakan kependidikan, respon umat Buddha yang mempengaruhi peranan kebijakan kependidikan sekolah minggu Buddha di masa pandemic covid-19.